PROSPEK SAHAM PERBANKAN DI INDONESIA - Iwan Kusmayadi; Muhammad Ahyar; Muhdin Muhdin; G. A. Oktaryani (JMM UNRAM - MASTER OF MANAGEMENT JOURNAL, 2020)
The focus of this research is to determine stocks provide the highest profit (gain opportunity) for investors. Investors will compare opportunities in choosing investment in the banking sector by comparing the combination of long-term growth rates rather than bank fundamentals with stock valuations. The population in this study is banking stocks included in the LQ45 index. The method of data collection uses a sample survey with a purposive sampling technique with the criteria of banking stocks with the largest market capitalization and has a high level of liquidity in trading values, and has consistently been included in the LQ45 index for the last 10 years (2008 to 2017). The number of samples selected were 4 banks consisting of Bank Mandiri (BMRI), Bank BRI (BBRI), Bank BCA (BBCA), and Bank BNI (BBNI). Data collection techniques through documentation, as well as quantitative data sourced from secondary data. Data analysis techniques by comparing the growth of fundamental performance such as Return On Assets (ROA), Return On Equity (ROE), Debt to Equity (DER), Capital Addequacy Ratio (CAR), and Non Performing Loans (NPL). Whereas market performance through Share Price, Earning Per Share (EPS), Price Earning Ratio (PER), Price to Earning Growth (PEG), and Dividend Yield by using compounded annual growth rate (CAGR). Then compare the value of the Margin Of Safety (MOS) Average in stock valuation analysis. The results of this study indicate that the financial performance of Bank BCA (BBCA) is superior to other banks according to DER, CAR and NPL. BRI is the best bank in generating profitability (ROA and ROE) compared to 3 other banks. Meanwhile, according to the stock market performance based on the order of the greatest opportunity level, Bank BNI has the best prospects because it has the largest EPS growth, the lowest stock price valuation, and sufficient MOS value, then ranked below it respectively are Bank Mandiri, Bank BRI, and Bank BCA .Keywords:Financial performance, market performance, and stock value